PENGEMBANGAN MEDIA PEMBELAJARAN WORDLESS PICTURE DENGAN KOMPUTER UNTUK KECAKAPAN WRITING DI PONTIANAK - Bahri, Syaiful (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research and development is to produce a package of learning and skill learning media for writing skill using wordless picture-based media computer Â the researcher also use some tools of data collection such as guide interview, observation checklist, which now facilitates all necessary data can be obtained from the results of the interview, observation and question form distribution during the learning process. After all the process were completed in this research, so there are several findings, namely, the products of learning media in the form of skills writing using wordless picture with computer-based in the form of a Power point presentation gained a positive responses from students as users and language teachers. In addition, both in terms of presentation materials, instructional design and media used, get a good appraisal from experts so worthy to be used as a product in research development.Keywords: Learning Media, writing prowess, wordless picture.